Awareness, Knowledge, and Perception of Tooth-Supported and Implant-Supported Prostheses among Adults in Sana'a City: A Survey-Based Study - Aqram Al-Fareh; Mohammed Dubais; Ahlam Smran; Shadi El Bahra; Abdulaziz Samran (MDPI AG, 2023)
The study aimed to evaluate knowledge, awareness, and perception of tooth-supported and implant-supported prostheses among an adult sample in Sana'a city in Yemen. A cross-sectional descriptive-analytical study was conducted on a convenient sample of 509 participants. All participants were aged 18 years and above with at least 1 missing tooth. The participants visited the public or private hospitals or their outpatient clinics in the municipality of the capital, Sana'a, Yemen. Their chief complaints when visiting the hospitals were not related to dental problems but to general healthcare. The participants who agreed and signed the consent form were interviewed and examined. The data were then recorded and statistically analyzed. The levels of awareness and knowledge of implant-supported prostheses among the 509 participants were low (58.0%, 33.6%, respectively). A significant positive correlation was found between genders (p = 0.003 for males, p = 0.000 for females), but no significant differences were detected between genders related to the awareness and knowledge of tooth-supported prostheses (p = 0.690). Most of the respondents had a low level of awareness, knowledge, and perception of treatment options for tooth replacement modalities.